The Black Awakening and Reconstructing the black Identity through Pan-Africanism in John Oliver Killens’ ‘The Minister Primarily’ (International Journal of Food and Nutritional Sciences, 2022)
John Oliver Killens’s ‘The Minister Primarily’ is socio-political satire in American and African contexts. The novel is anti-colonists in nature. It focuses on international political relationship between America and the Independent People’s Democratic Republic of Guanaya, an imaginary nation. John Oliver Killens explicitly focuses on nationalism and Pan-Africanism. He gives a message to the black community that the Pan-Africanism is the only solution to overcome their inferiorities. It teaches them to love their black beautiful soul, respect and nurture the African culture. Through this novel, Killens attempts to show how colonialism has imposed its will on the people of Guanaya and other nations in Africa, and how this has led to their exploitation and oppression. He suggests that the only way for the African Diaspora to overcome this is through Pan-Africanism, a movement that aims to unite all people of African descent and promote African pride, self-determination, and liberation. The research paper locates Nationalism and Pan-Africanism movement is a global movement.